Improving Vitamin D Screening in a Pediatric Rheumatology Clinic Using Structured Quality Improvement Process. Issue 5 (8th September 2022) - Sarkissian, Aliese; Oberle, Edward; Al Ahmed, Ohoud; Piccinich, Dawn; Barbar-Smiley, Fatima; Zak, Helen; Sivaraman, Vidya
Abstract : Introduction: Monitoring levels of 25-hydroxyvitamin D (25-OHD) is an integral part of bone health assessment in the general pediatric population, especially in at-risk populations such as children with juvenile idiopathic arthritis (JIA), childhood-onset systemic lupus erythematosus (c-SLE), and juvenile dermatomyositis (JDM). However, only 38% of the patients with JIA, c-SLE, and JDM receiving care at Nationwide Children's Hospital Rheumatology clinic in 2016 had a 25-OHD level ordered in the preceding year. The objective of this project was to increase the percentage of 25-OHD levels ordered in patients with JIA, c-SLE, and JDM from 38% to 80% in 11 months and sustain it for 6 months. Methods: A multidisciplinary team initiated a continuous improvement project utilizing the Lean Six Sigma methodology. The team diagrammed the clinical process and identified steps that needed improvement. In addition, the team completed a root cause analysis of the process and brainstormed subsequent countermeasures. Results: The team did not meet the 80% target but did order a 25-OHD level on 61% of patients by the end of the study period compared to 38% at the start of the study ( P value 0.001). The level was sustained after the study period, with 68% of these children having a 25-OHD level ordered. Conclusion: The team successfully improved the screening processes for vitamin D deficiency in a busy subspecialty clinic setting using Lean Six Sigma methodology.